2021
DOI: 10.1126/sciadv.abf4741
|View full text |Cite
|
Sign up to set email alerts
|

Relations between absorption, emission, and excited state chemical potentials from nanocrystal 2D spectra

Abstract: For quantum-confined nanomaterials, size dispersion causes a static broadening of spectra that has been difficult to measure and invalidates all-optical methods for determining the maximum photovoltage that an excited state can generate. Using femtosecond two-dimensional (2D) spectroscopy to separate size dispersion broadening of absorption and emission spectra allows a test of single-molecule generalized Einstein relations between such spectra for colloidal PbS quantum dots. We show that 2D spectra and these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(65 citation statements)
references
References 73 publications
6
53
0
Order By: Relevance
“…Indeed, a very recent paper has proposed a method to analyze ultrafast, 2D spectroscopy measurements and estimate the chemical potential of photoexcited states, and applied it to larger PbS nanocrystals. 95 Similar approaches have historically encountered challenges in capturing the behaviour of molecular systems, 95,98 where structural fluctuations/reorganization are significant. We note that analogous concerns are expected for ultra-small 0D semiconductor materials where few atoms experience a bulk-like environment, particular given the possibility that defect states 49 involving surface reconstruction are involved in the photophysics.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a very recent paper has proposed a method to analyze ultrafast, 2D spectroscopy measurements and estimate the chemical potential of photoexcited states, and applied it to larger PbS nanocrystals. 95 Similar approaches have historically encountered challenges in capturing the behaviour of molecular systems, 95,98 where structural fluctuations/reorganization are significant. We note that analogous concerns are expected for ultra-small 0D semiconductor materials where few atoms experience a bulk-like environment, particular given the possibility that defect states 49 involving surface reconstruction are involved in the photophysics.…”
Section: Resultsmentioning
confidence: 99%
“…S29 †). 20,26,[59][60][61] The polydispersity accounts for $20% of the linewidth at all sizes and is not inuenced by the temperature despite the signicantly shorter nucleation times at high temperature (Fig. 7B and S28-S30 †).…”
Section: Nucleation Time and Polydispersitymentioning
confidence: 95%
“…Further consideration of SX measurement proves it powerful in testing another debated aspect of NC photophysics concerning the development of optical gain. The limited success of applying NCs as a laser gain medium due to continued absorption at the BE and limited lifetimes of MXs has been discussed broadly. Recently, Jonas and co-workers have detected contributions of stimulated emission in PbS NCs excited with a single exciton using 2D electronic spectroscopy . They concluded that even in situations where no net optical gain is achieved the projection of emission correlations in 2D allows the effects of stimulated emission to be separated out.…”
Section: Searching For Stimulated Emission With Sxmentioning
confidence: 99%
“…32−34 Recently, Jonas and co-workers have detected contributions of stimulated emission in PbS NCs excited with a single exciton using 2D electronic spectroscopy. 35 They concluded that even in situations where no net optical gain is achieved the projection of emission correlations in 2D allows the effects of stimulated emission to be separated out. Here we apply SX measurements for the same purpose.…”
Section: Sxmentioning
confidence: 99%